Study of Adaptive Behaviors in People with Mental Retardation - Mahfooz, Mujtaba (Integrated Journal for Research in Arts and Humanities, 2024)
Coping with the pressures of life and acquiring personal and social skills have always been a part of the realities of human life and have been manifested in different forms in different periods of life. Conflicts do not show much in childhood, but with age and when facing the special difficulties of adolescence and youth, internal and environmental conflicts become more apparent. Therefore, if people master daily life skills and social responsibilities from childhood, they will perform well in stressful situations. The current research is designed to investigate adaptive behaviors in mentally retarded people. Because, the knowledge and awareness of educational specialists, parents and educators regarding the adaptive behaviors of children and also the use of different methods in facing problems and situations can be effective in dealing with them and forming adaptive behaviors and can affect different aspects of their lives. The present research is descriptive-analytical which was done in the form of a library. The tools for collecting information in this research are psychology books, research articles and reputable national and international scientific journals. Researches findings show, early assessment and interventions have a significant impact on the development of children's adaptive behaviors from an early age. This awareness can be a great help in planning and designing educational models for these children in the field of adaptive skills and problem solving.